Preaching prevention : born-again Christianity and the moral politics of AIDS in Uganda - Boyd, Lydia (Perspectives on global health., 2015)
Preaching Prevention examines the controversial U.S. President's Emergency Plan for AIDS Relief (PEPFAR) initiative to "abstain and be faithful" as a primary prevention strategy in Africa.